Jatropha deoiled cake filler‐reinforced medium‐density polyethylene biocomposites: Effect of filler loading and coupling agent on the mechanical, dynamic mechanical and morphological properties. Issue 5 (27th March 2013) - Elshaarani, M.T.; Yaakob, Z.; Dahlan, K.Z.M.; Mohammad, M.
Abstract This work focuses on the performance of Jatropha deoiled cake (JOC) as filler for medium‐density polyethylene. The biocomposites were prepared using a melt‐compounding technique. Maleated polyethylene (MPE) was used as a reactive additive to promote polymer/filler interfacial adhesion. The mechanical, thermodynamic mechanical and morphological properties of the resultant composites were investigated. The results show that the incorporation of JOC into the matrix reduced tensile, flexural, and impact strengths compared with the pure matrix. Moreover, tensile and flexural moduli were increased. The composites prepared with MPE had better mechanical properties and lower water uptake, indicating an enhancement in the interfacial interaction between JOC and polyethylene systems. The storage modulus was increased by the increase in filler loading and decreased when MPE was used. The composites loss modulus curves revealed two glass transitions indicating partial miscible blends. Scanning electron microscopy analysis for maleated composites showed a relatively homogeneous morphology with few left cavities, and the filler particle size is smaller compared to nontreated composites. POLYM. COMPOS., 2013. © 2013 Society of Plastics Engineers